From customer orientation to social CRM. New insights from Central Europe - Bachmann, Pavel; Kantorová, Kateřina (Univerzita Pardubice, 2016)
In the context of the gradual virtualization of social relationships, the traditional form of relationship management has begun to change. Original concept of customer relationship management (CRM) based rather on face-to-face and offline communication in the physical environment is converting into social CRM (SCRM), where the contact through social networks and relationships within online communities. Therefore, the paper aims to analyse SCRM in medium and large businesses based on the primary research. Research sample (N=81) includes medium and large enterprises operating in the Czech Republic. The findings showed that sampled firms perceived the digital marketing as slightly more important than the traditional type of marketing. More than nine-tenth of companies considered CRM to be a significant marketing tool for their own practice. Subsequently, SCRM was perceived as significant by approximately two-thirds of respondents. Czech enterprises practice rather investigation of external online communities and contributing to them than building their own internal online community. Finally, the social sites are in this process used rather for short-term communication with the customer than for the purpose of self-promotion or data mining. Furthermore, some differences were found in approach to digital marketing, CRM, and SCRM between consumer oriented and business oriented organizations.
Keywords: customer relationship management; social CRM; social media; business intelligence; Czech Republic; M310; M15; C8